1994
DOI: 10.1557/proc-360-45
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Barium Strontium Titanate and Non-Ferroelectric Oxide Composites

Abstract: Various composites of BSTO combined with other nonelectrically active oxide ceramics have been formulated. In general, the composites have adjustable electronic properties which can be tailored for use in various electronic devices. Two applications, which are of interest in regard to the composites being discussed here, are phased array antennas and capacitor-varistor monolithic devices. For the phased array antennas, these properties include reduced dielectric constants, ε′, where ε = ε′ - iε″, and loss tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The materials are bulk oxide-ceramic composites of barium strontium titanate oxide (BSTO). ARL has also developed a simple, low-cost processing technique for their manufacturing [6]- [8]. It involves mixing barium titanate (BaTiO ) and strontium titanate (SrTiO ) powders.…”
Section: Ferroelectric Materialsmentioning
confidence: 99%
“…The materials are bulk oxide-ceramic composites of barium strontium titanate oxide (BSTO). ARL has also developed a simple, low-cost processing technique for their manufacturing [6]- [8]. It involves mixing barium titanate (BaTiO ) and strontium titanate (SrTiO ) powders.…”
Section: Ferroelectric Materialsmentioning
confidence: 99%
“…Our recent inquiry into those losses [6,7] indicated that the possibility of developing ferroelectric materials with losses low enough to be useful for traveling wave antenna is remote. For these reasons, our efforts are being concentrated in developing a ferroelectric lens, which is discussed in the next section.…”
Section: Fig 6 Basic Configuration Of the Ferroelectric Lensmentioning
confidence: 99%